Federated Learning and Deep Reinforcement Learning Synergy: Opportunities for Multi-Cloud Serverless Deployment - I Gusti Ngurah Wikranta Arsa Arsa; Arief Setyanto; Andi Sunyoto; Alva Hendi Muhammad (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2026)
The Development of distributed computing has enabled the use of multi-cloud and serverless computing, which are beneficial due to their flexibility, scalability, and cost efficiency. There are, of course, pertinent challenges associated with these computing paradigms, such as resource heterogeneity, cold-start latency, vendor lock-in, and privacy. Recent trends in Federated Learning (FL) and Deep Reinforcement Learning (DRL) hold promise in solving these issues. FL systems enable decentralised, privacy-preserving model training across heterogeneous systems, while DRL systems enable adaptive models for real-time decision-making to optimise system resources and improve performance. This Systematic Literature Review (SLR) covers the years 2020 to early 2026 and examines the intersection of FL and DRL in multi cloud serverless computing, following the PRISMA methodology. A primary analysis of 50 quality studies was undertaken to answer four privacy-related resource management questions. The results showed FL improves privacy and scalability using decentralised training. Consolidating the Federated DRL and Multi-Agent stacks enhances the system by achieving a better trade-off and optimization among latency, energy, and operational efficiency. However, a few gaps still exist, such as the absence of a more holistic framework, elusiveness in cross-system integration and collaboration, and a lack of concrete real-world applications. More work is needed to build a cohesive Federated Learning framework to improve sustainability and security in the multi-cloud, serverless systems of the future. This examination provides a solid foundation for the Development of innovative, privacy-preserving, and dynamic resource management in future cloud computing environments.